2020
DOI: 10.35905/banco.v2i1.1331
|View full text |Cite
|
Sign up to set email alerts
|

Harga Jual Dan Tingkat Margin: Preferensi Nasabah Dalam Menggunakan Produk Pembiayaan Murabahah BMT As’adiyah Sengkang

Abstract: Penelitian ini akan membahas tentang pengaruh harga jual dan tingkat margin terhadap keputusan pelanggan untuk menggunakan produk murabahah BMT As'Adiyah Sengkang. Tujuannya adalah untuk mengetahui apakah biaya barang dan tingkat margin memiliki pengaruh yang signifikan bagi pelanggan menggunakan produk murabahah di BMT As'Adiyah Sengkang. Jenis penelitian ini menggunakan jenis penelitian kuantitatif dengan menggunakan analisis statistik deskriptif dan akan ditafsirkan menggunakan uji regresi linier berganda. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Such dilemmas that frequently arises in murābaha financing at sharia banks is the assumption that margin in murābaha financing is more expensive than interest rate in conventional-credit banks (Furwanti, 2020;Maulidizen, 2018;Pratiwi et al, 2015). The closest statement was expressed by Maulidizen (2018) in his research, revealed that community believe that sharia bank was always entirely compatible with low prices based on the results of interviews with respondents.…”
Section: Criticism Of Margin Actualization In Murābahah Financing At ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Such dilemmas that frequently arises in murābaha financing at sharia banks is the assumption that margin in murābaha financing is more expensive than interest rate in conventional-credit banks (Furwanti, 2020;Maulidizen, 2018;Pratiwi et al, 2015). The closest statement was expressed by Maulidizen (2018) in his research, revealed that community believe that sharia bank was always entirely compatible with low prices based on the results of interviews with respondents.…”
Section: Criticism Of Margin Actualization In Murābahah Financing At ...mentioning
confidence: 99%
“…Furthermore, sharia bank does not give such advises to the custumer relating to the changing margin adjustment at each payment maturity, causing the customer feels burdened by this situation (Wawancara Nasabah Bank Syariah yang Menggunakan Akad Murabahah, 2021). Furwanti's (2020) reported that although the sharia financial institution provides margin negotiation opportunities, it still prioritizes margin determination decisions based on conditional factors such as installment time periods and customer characteristics, thus negotiations play a minor role in determining margin levels (Furwanti, 2020).…”
Section: Criticism Of Margin Actualization In Murābahah Financing At ...mentioning
confidence: 99%